ChemInform Abstract: Reactions of 1, 2‐Cyclopropyl Carbohydrates. Issue 2 (January 2015) - Harvey, Joanne E.; Hewitt, Russell J.; Moore, Peter W.; Somarathne, Kalpani K.
Abstract Review: progress in the synthesis and reactions of 1, 2‐cyclopropyl carbohydrates since 2000